Exploring Investment Behaviour: the Role of Personality, Risk Preferences, Financial Literacy, and Demographics - Jurita, Adela-Adriana; Lazar, Paul Sorin; Butoi, Elisabeta; Pop, Atanasiu Iustin; Dragomir, Cristina (Transformations In Business & Economics, 2025)
This study explores the impact of personality traits, risk preferences, financial literacy, and demographics on investment behaviour in Romania, addressing a gap in understanding how these factors interact in an emerging market context. Using survey data from 1,171 respondents, it applies multinomial logistic regression to analyse preferences for stocks, cryptocurrencies, real estate, and banking products. The study is original in its integration of psychological traits and socio-economic factors with a focus on high-risk assets like cryptocurrencies, a topic underexplored in existing research. Results show openness and extraversion significantly influence preferences for innovative and tangible assets, while financial literacy plays a key role in promoting informed investment decisions. Urban and younger investors lean toward innovative investments, while older and risk-averse individuals prefer traditional options. Policy implications suggest prioritising targeted financial education to improve literacy and fostering inclusive investment opportunities to reduce disparities across demographic groups.